The Effect of the Imitative Writing Method on Early Writing Skills of Grade I Elementary Students - Tarman Tarman; Ratnawati Ratnawati (Universitas Sulawesi Barat, 2026)
The low level of early writing skills among elementary students (letter completeness, proportion, neatness, speed) is exacerbated by conventional methods relying solely on static copying without movement demonstration or feedback. This study examines the effect of the Imitative Writing method on improving these skills. This quasi-experimental nonequivalent control group design involved 48 first-grade students from Manggarupi Islamic Elementary School. The experimental group (n = 25) received Imitative Writing over 8 sessions (demonstration, guided imitation, direct feedback), while the control group (n = 23) used conventional static copying. Writing skills were measured with a valid 10-word test (CVR = 0.85) and reliable (inter-rater reliability = 0.88). Data were analyzed via normality, homogeneity, independent t-test, and N-Gain. Results showed the experimental group's mean posttest (81.6) was significantly higher than the control (64.3); t(46) = 9.43, p = 0.000, Cohen's d = 2.78 (very large effect). The experimental N-Gain was moderate (0.61), control low (0.24), with highest improvement in letter completeness (1.7 points). Therefore, Imitative Writing is proven effective with a very large effect on improving first-grade early writing skills. Implications: teachers should demonstrate writing, provide letter-by-letter feedback, and use large-lined exercise books. These findings also reinforce Bandura's social learning theory and Vygotsky's scaffolding principle in early literacy.